1999
DOI: 10.1002/(sici)1097-0215(19990719)82:2<171::aid-ijc3>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for adenocarcinoma of the small intestine

Abstract: We have investigated the relation between alcohol, tobacco and dietary habits and risk of adenocarcinoma of the small intestine using data from 2 hospital‐based case‐control studies on intestinal cancers conducted in 6 Italian centres between 1985 and 1996. Cases were 23 patients below age 75 years with adenocarcinoma of the small intestine. Controls were 230 patients admitted to hospital for a wide spectrum of acute, non‐neoplastic, non‐digestive tract diseases, matched to cases on sex, age, study and centre.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
89
1
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 17 publications
7
89
1
4
Order By: Relevance
“…Further, data from two Italian hospital-based case -control studies suggested an inverse relationship (Negri et al, 1999). However, only 23 cases were examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, data from two Italian hospital-based case -control studies suggested an inverse relationship (Negri et al, 1999). However, only 23 cases were examined.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for small bowel cancer, however, include dietary factors, cigarette smoking, alcohol intake and different medical conditions (Neugut et al, 1998). Further, adenocarcinomas of the small and large bowel share several common features, and it has been shown that there is a strong similarity between the dietary correlates of risk of adenocarcinoma of the small intestine and colon cancer (Negri et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Small intestinal carcinomas share morphological characteristics and risk factors with other gastrointestinal carcinomas, especially with colorectal carcinomas (Negri et al, 1999;Neugut et al, 1998). Both tumour types may arise from pre-existing adenomas and both are reported to occur more frequently in patients with chronic in¯ammatory bowel diseases (Pohl et al, 2000;Logan et al, 1989;Lennard-Jones et al, 1977) and in patients with hereditary gastrointestinal cancer prone syndromes like familial adenomatous polyposis coli (FAP), hereditary non polyposis colorectal cancer syndrome (HNPCC), and Peutz-Jeghers syndrome (Neugut et al, 1998;Park et al, 1999;Spigelman et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…with de novo cancers that were found in 60-69-year-olds [15] . Tumors were found in the ileum at a rate of 75%.…”
Section: Discussionmentioning
confidence: 97%